Impacts of COVID-19 on the central nervous system - Camargos, Alice Borém; Santos, Ana Carolina Araújo Lage; Alagia, Antônio Victor Condez; de Almeida, Beatriz Melo; Teixeira, Izabel Brito; Milhomem, José Victor Mendes; Feio, Júlia Couto; Bar, Stael Fernandes (Seven Editora, 2023)
Introduction: COVID-19 is an infectious disease caused by the SARS-Cov-2 virus, of the beta-coronavirus clade, which mainly affects the human respiratory system. This pathology has been the subject of high demand for studies since the beginning of its dissemination. But, despite a large number of cases related to its pulmonary involvement, the growing number of extrapulmonary and, mainly, neurological symptoms reported by a large part of the literature should not be ignored. Objective: To assess the impacts of COVID-19 on the Central Nervous System according to viral mechanisms and their long-term consequences. Material and methods: The study was carried out from a literature review based on data published in the CAPES Portal, SciELO, and PubMed using, in the research, descriptors related to COVID-19, neurological manifestations, and the Nervous System. 50 articles were collected, 26 of which were discarded. The inclusion criterion was the correlation made between COVID-19 and Central Nervous System disorders, and the exclusion criterion adopted was the language of the articles, selecting only those in Portuguese or English. Literature review: Taking into account the genomic similarities between the SARS-Cov and SARS-Cov-2 viruses, the finding of both in the cerebrospinal fluid demonstrates their undoubted ability to enter and, therefore, cause damage to the Central Nervous System. From these similarities, it was possible to determine some mechanisms of neurological invasion of SARS-Cov-2, such as the use of glycoproteins of the spike present in its structure to form bonds with ACE2 receptors of host cells, thus penetrating cells such as neurons, neuroglia, and endothelial cells, where it enters the blood-brain barrier. Furthermore, other damage caused by the virus outside the CNS, such as gas exchange disruptions and cytokine storms, can indirectly affect this system, causing some damage. Studies indicate that 40% of infected patients develop neurological symptoms, such as anosmia and ageusia, and other symptoms linked to brain dysfunction, such as headaches, dysphoria, mental disorders, and delirium. Thus, the use of neurological symptoms as signs of suspicion and isolation of individuals is a possible aid factor for reducing contagion and early diagnosis. In addition, among the rare events of the severe form of the disease, we can mention cases of cerebral hemorrhages, stroke, and even Alzheimer's, Parkinson's, and Multiple Sclerosis. However, due to the current situation of COVID-19, it is still difficult to investigate its long-term sequelae. Final considerations: Therefore, health professionals should be informed and aware of the possible involvement of this virus in the CNS, submitting affected individuals to clinical, laboratory, and radiological examinations in advance for neurological evaluation. Finally, future research on possible long-term sequelae is extremely important for the development of intervention and monitoring strategies for these individuals.DOI: https://doi.org/10.56238/devopinterscie-023